The Influence of Transaction Channel Preference and Cash Handling Behavior on the Achievement of Cash Donations in the ‘Charity Box Personal’ Program (A Research at the Humanitarian Organization Kilau Indonesia) - Akhmad Sugandi; Yoyo Sudaryo; Nunung Ayu Sofiati; Mochammad Mukti Ali; Gurawan Dayona Ismail (Green Publisher Indonesia, 2025)
The rapid digitization of financial transactions in Indonesia has fundamentally altered consumer payment behaviors, creating significant challenges for traditional cash-based charitable fundraising methods. This research investigates how donors’ Transaction Channel Preference and Cash Handling Behavior shape Cash Donation Achievement in Kilau Indonesia’s “Charity Box Personal” program. Using a cross-sectional survey of N=200N=200 donors sampled via stratified random procedures across four West Java regencies, Likert-type measures for both predictors were converted to interval scales with the Method of Successive Intervals (MSI). Multiple linear regression with SPSS 27 indicates a significant model fit (R=0.817R=0.817; R2=0.667R2=0.667; F(2,197)=197.233F(2,197)=197.233, p<.001p<.001). Transaction Channel Preference negatively predicts cash donations (β=−0.614β=−0.614, p<.001p<.001), consistent with a channel-substitution mechanism as donors favor digital payments. Contrary to expectation, Cash Handling Behavior also shows a negative association (β=−0.538β=−0.538, p<.001p<.001), suggesting that stricter cash budgeting reduces ad-hoc giving opportunities. Diagnostics (Durbin–Watson ≈ 1.94; no notable multicollinearity) support model validity. Managerially, nonprofits should adopt an omnichannel strategy by integrating QRIS into physical boxes and reporting combined (cash + digital) metrics. Theoretically, findings connect UTAUT, Perceived Value, and the Theory of Planned Behavior to explain declining cash-based philanthropy in a rapidly digitizing context.